Countering the Cognitive, Linguistic, and Psychological Underpinnings Behind Susceptibility to Fake News: A Review of Current Literature With Special Focus on the Role of Age and Digital Literacy - Gaillard, Stefan; Oláh, Zoril A.; Venmans, Stephan; Burke, Michael (Frontiers in Communication, 2021)
Fake news poses one of the greatest threats to democracy, journalism, and freedom of expression. In recent cases, fake news’ designs are to create confusion and lower trust among the general public—as seen in the 2016 United States presidential campaign and the Brexit referendum. The spread of information without formal verification increased since the introduction of social media and online news channels. After the popularization of fake news, researchers have tried to evaluate and understand the effects of false information from multiple different perspectives. However, it is evident that to tackle the problem of fake news, interdisciplinary collaboration is needed. This article evaluates the main findings of recent literature from an integrated psychological, linguistic, cognitive, and societal perspective, with a particular focus on digital and age-related aspects of fake news. From a psychosociological standpoint, the article provides a synthesized profile of the fake news believer. This profile generally denotes overconfidence in one’s ability to assess falsehoods due to a human need for causal explanations. The fake news believer can be described as well-intentioned and critical, yet driven by a basis of distrust and false foundational knowledge. Within linguistics, manual analytical tools exist to understand the persuasive tactics in fake news. The article takes analytical techniques from both the humanities and the social sciences, such as transitivity analysis, Hugh Rank’s language persuasive framework, and others that can be used to analyze the language used in the news. However, in the age of big data perhaps only computational techniques can adequately address the issue at the root. While this proves successful, there are hurdles like the ambiguity of satire and sarcasm, manual labeling of data, and the supple nature of language. Reading comprehension differences between digital versus paper reading seem inconclusive. There are, however, notable behavioral and cognitive differences in reading behavior for the digital medium such as more scanning, less sustained attention, cognitive retreat, and shallower processing. Interestingly, when metacognitive strategies were probed by, for example, having participants independently allocate reading time, a difference in comprehension scores started to emerge. Researchers have also found accounts of differences due to medium preference; and on average older people seem to prefer paper reading. Cognitive retreat, shallow processing, and overconfidence associated with digital reading and the digital medium, in general, might make readers less likely to engage in the cognitive effort fake news detection requires. Considering that there are clear cognitive differences between older generations and younger generations (in terms of decreased processing speed, metacognition, and ability to multitask) differences in how these generations process fake news is plausible. Regrettably, most current research into psychological factors influencing susceptibility to fake news does not take into account age differences. Our meta-analysis showed that 74% of behavioral studies looking at fake news largely ignore age (N = 62), even though voter turnout was far higher among older generations for both the 2016 United States presidential election and the 2016 United Kingdom European Union membership referendum. Many provisional programs set up in the past few years aimed at training digital literacy, reading comprehension, and asking critical questions as virtual skills to detect fake news. These training programs are, however, mostly aimed at younger – digitally native – groups. As a result, these efforts might not be as efficacious as intended and could be improved upon significantly. This article argues that age must become a larger focus in fake news research and efforts in educating people against fake news must expand outside of the universities and isolated areas and include older generations.